Estimation of the Power Spectrum of Electrocardiosignals - Kirmonas, A. (Elektronika ir Elektrotechnika, 2000)
Estimation of the power spectrum band of electrocardiosignals is based on the analysis of QRS complexes approximated by first order polinoms. The function for approximation of QRS complexes is proposed and the mathematical expression of the power spectrum function of approximated QRS complexes is obtained. Calculation results of mean spectrum function of 210 approximated QRS complexes are presented.